KEPEMIMPINAN TRANSFORMASIONAL KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU DI SEKOLAH - Eko Siswanto; Lilik Muslichati; Siti Mundrikah; Ngurah Ayu Nyoman M (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to explore the role of transformational leadership by school principals in improving teacher performance at both primary and secondary education levels, based on a review of several literature sources. The findings indicate that: (1) there is a significant and positive influence of principals' transformational leadership on teacher performance at both primary and secondary school levels; (2) transformational leadership by school principals can enhance teachers' commitment and performance in implementing the Merdeka Belajar (Independent Learning) curriculum; and (3) transformational leadership improves teacher performance through four key dimensions: idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration. These findings highlight the crucial role of school principals as transformational leaders in fostering optimal teacher performance.